Pengaruh Brand Ambassador dan Green Marketing terhadap Brand Equity Pond's (Unilever) yang dimediasi oleh Brand Trust: (Studi pada Pembeli Generasi Z Di Kota Makassar) - Widianti, Reski; Nofri, Okta; Awaluddin, Awaluddin (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
This research aims to find out whether brand ambassadors and green marketing influence Unilever's brand equity (Pond's) with brand trust as a mediating variable in generation Z in Makassar City. This research is quantitative research with an associative research approach. The population in this study is all generation Z who have used or purchased Pond's products in Makassar City with a sample of 120 respondents. The sampling technique uses the Hair formula, namely the number of indicators multiplied by 5 to 10. This research uses primary data in the form of questionnaires distributed. The research instrument used was a Likert scale. The analysis method used is SmartPLS.4. The results of this research show that the brand ambassador variable has a positive and significant effect on brand trust. The brand ambassador variable has a positive and significant effect on brand equity. The green marketing variable has a positive and significant effect on brand trust. The green marketing variable has a positive and significant effect on brand equity. The brand trust variable has a positive and significant effect on brand equity. Brand trust mediates the influence of brand ambassadors on brand equity (Pond's). Brand trust mediates the influence of green marketing on brand equity (Pond's). Keywords: Brand, brand ambassador, green marketing, brand equity, brand trust, pond's, Unilever, and generation Z.